International study on antidepressant prescription pattern at 20 teaching hospitals and major psychiatric institutions in East Asia: Analysis of 1898 cases from China, Japan, Korea, Singapore and Taiwan - Uchida, N. (2016)
10.1111/j.1440-1819.2007.01702.x